Expérimenter et documenter le live sur les plateformes : les pratiques des fans du groupe Indochine - Laure Bolka-Tabary (Communiquer)
Based on an ethnosemiotic study of two concerts broadcast in livestream in 2019 and 2020 by the Indochine music band, we observe how fans express themselves about live performances and how they document them on Twitter and Instagram. Through the analysis of their publications and comments, we study which images of these concerts are published, “redocumentarized”, and what meaning and emotions are carried in these publications. The two platforms are places for sharing opinions and emotions. They show that the live experience is lived by anticipation and by extension, and that logics of collection coexist with self-visibility and promotion of the beloved artists.